Rediscovery and redescription of the abyssal squat lobster Munidopsis petalorhyncha Baba, 2005 (Crustacea: Decapoda: Munidopsidae) from the Northwest Pacific - Komai, Tomoyuki; Marin, Ivan; Kakui, Keiichi (Zootaxa, 2017)
A poorly known abyssal squat lobster, Munidopsis petalorhyncha Baba, 2005 [= Munidopsis subsquamosa latimana Birstein & Zarenkov, 1970], is redescribed on the basis of the holotype from the Kuril Trench at depths of 5060–5130 m and two recently collected specimens from off Japan at depths of 5353–5382 m. Examination of those specimens enabled us to reassess diagnostic characters of the species. Munidopsis petalorhyncha appears closest to M. thieli Türkay, 1975, known from abyssal plain of the eastern Atlantic, but the spinulose lateral margins of the rostrum, the presence of a distinct lateral eye spine, the presence of a distomesial spine on article 3 of the antennal peduncle and spinose ventral (flexor) margins of meri of pereopods 2–4 distinguish M. petalorhyncha from M. thieli.